Early-start antiplatelet therapy after operation in patients with spontaneous intracerebral hemorrhage and high risk of ischemic events (E-start): Protocol for a multi-centered, prospective, open-label, blinded endpoint randomized controlled trial - Wang, Kaiwen; Mo, Shaohua; Liu, Qingyuan; Pu, Jun; Huang, Xiaobin; Kang, Dezhi; Lin, Fixin; Zou, Dewei; Sun, Xinguo; Ren, Jinrui; Tong, Xianzeng; Li, Jiangan; et al. (Frontiers in Aging Neuroscience, 2022)
Background For severe spontaneous intracerebral hemorrhage (sSICH) patients with high risk of ischemic events, the incidence of postoperative major cardiovascular/cerebrovascular and peripheral vascular events (MACCPE) is notable. Although antiplatelet therapy is a potential way to benefit these patients, the severe hemorrhagic complications, e.g., intracranial re-hemorrhage, is a barrier for early starting antiplatelet therapy. Objectives This randomized controlled trial aims to identify the benefit and safety of early starting antiplatelet therapy after operation for sSICH patients with high risk of ischemic events. Methods This study is a multicenter, prospective, randomized, open-label, blinded-endpoint trial. We will enroll 250 sSICH patients with a high risk of ischemic events (including cerebral infarcts, transient ischemic attack, myocardial infarction, pulmonary embolism, and deep venous thrombosis). The participants will be randomized in a 1:1 manner to early-start group (start antiplatelet therapy at 3 days after operation) and normal-start group (start antiplatelet therapy at 30 days after operation). The early-start group will receive aspirin 100 mg daily. The control group will not receive antithrombotic therapy until 30 days after operation. The efficacy endpoint is the incidence of MACCPE, and the safety endpoint is the incidence of intracranial re-hemorrhage. Discussion The Early-Start antiplatelet therapy after operation in patients with spontaneous intracerebral hemorrhage trial (E-start) is the first randomized trial about early start antiplatelet therapy for operated sSICH patients with a high risk of ischemic events. This study will provide a new strategy and evidence for postoperative management in the future. Clinical trial registration ClinicalTrials.gov, identifier NCT04820972; Available at: https://clinicaltrials.gov/ct2/show/NCT04820972?term=NCT04820972&draw=2&rank=1. Chinese Clinical Trial Registry, identifier ChiCTR2100044560; Available at: http://www.chictr.org.cn/showproj.aspx?proj=123277.